Balancing regional industrial development: analysis on regional disparity of China's industrial emissions and policy implications. (10th July 2016) - Liang, Hanwei; Dong, Liang; Luo, Xiao; Ren, Jingzheng; Zhang, Ning; Gao, Zhiqiu; Dou, Yi
Abstract: Efficient industrial emissions mitigation strategy is critical for China's national action on climate change and sustainable development, considering its rapid industrialization. Regional disparity brings difficulties and uncertainties to policy implementation in China. Therefore, an investigation on the regional features of industrial emissions is critical to better decision makings. While to date, related studies have been rather few. This paper applies a spatial analysis on regional features of China's industrial emissions (SO2, NOx and PM2.5 and CO2 emission) in 31 provinces. Spatial autocorrelation and regression analysis are firstly conducted to identify the regional emissions patterns. The regional disparity and inequity is further analyzed with Lorenz curve and Gini coefficient approach. Analytical results verify the regional cluster effects and the emissions' sensitivity to the economic and industrial development, and highlight not only disparity, but also inequity exists. It is concluded that, there is a larger unequal distribution of GDP per unit of air pollutants and CO2 emission between eastern and western regions, reveals that less developed western and central regions suffer from the emission leakage and an environmental inequity. Regional oriented mitigation strategies are required to balance regional disparity, so as to realize the industrial emission control policy under the "equity and efficiency" principle. Highlights: Regional disparity of industrial emissions in China was investigated. Spatial analysis was integrated with Gini coefficient. Regional inequity and compensation measures were discussed. Regional oriented emission control policies were proposed.